INTERNALISASI NILAI MULTIKULTURAL DALAM MEMBENTUK SIKAP MODERASI BERAGAMA SISWA DI MADRASAH IBTIDAIYAH NEGERI 1 KOTA MALANG - Fita Mustafida; Mohammad Afifulloh; Abd. Gafur (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2023)
This paper aims to describe and analyze multicultural values that develop in Madrasah Ibtidaiyah Negeri I Malang City, as well as the process of multicultural values shaping students' attitudes toward religious moderation. The choice of research location is considered appropriate because MIN I Malang City has provided evidence of the incorporation of multicultural values, as enshrined in the philosophy of multiculturalism, into religious education and moderation education practices. This is evidenced by the inclusion of the principles of multicultural education into scholastic and community efforts, as well as the internalization of moderation values in curricular planning and implementation, so as to be able to manage the diversity of madrasah residents with an attitude of accepting differences so that they can live together in a harmonious school environment. With a qualitative approach, data collection is done through observation, interviews, and documentation. While data analysis uses the Milles Huberman model of data condensation, display, and conclusion, The results of this study found five multicultural values developed in MIN I Malang City: 1) religion, 2) Harmony, 3) Tolerance, 4) Equality, and 5) Cooperation. Meanwhile, the internalization of multicultural values in shaping attitudes of religious moderation is carried out through inculcating values in madrasah policies, curriculum, and learning, exemplary and habituation of moral culture, ubudiyah character, and Islamic culture